The Impact of The Prophetic Legal Policy on Thenumbness Diplomacy and Contemporary International Relations: an Analytical Study - Musaddad, Aliyu Ibrahim (IKONOMIKA, 2021)
The policy of the Prophet's legitimacy their role in  The development, progress and culture of what is known today as diplomacy and international relations. andThe policy of the Prophet's legitimacy It means the policy of the Messenger, may God bless him and grant him peace, and the management of diplomatic relations in times of peace and war, and the relationship with enemiesThis isthe paper about The study inAnalyze it. The researcher chosecurriculum TheShowy Analytical, as he talked about Five points from The impact of the policy of the Messenger, may God’s prayers and peace be upon him, in the progress of what is known in our timeDiplomacy and international relations in the light of legitimate politics. In the end it will come to an end Manaljoulesit's up to you tofor politicslegitimacy Effect great and important role in progress Contemporary diplomacy and international relations Especially since the Congress of Vienna in 1815